2006
DOI: 10.1007/s10534-006-9024-0
|View full text |Cite
|
Sign up to set email alerts
|

The overexpression of NADPH-producing enzymes counters the oxidative stress evoked by gallium, an iron mimetic

Abstract: Gallium (Ga), an iron (Fe) mimetic promoted an oxidative environment and elicited an antioxidative response in Pseudomonas fluorescens. Ga-stressed P. fluorescens was characterized by higher amounts of oxidized lipids and proteins compared to control cells. The oxidative environment provoked by Ga was nullified by increased synthesis of NADPH. The activity and expression glucose 6-phosphate dehydrogenase (G6PDH) and isocitrate dehydrogenase-NADP (ICDH) were stimulated in Ga-cultures. The induction of isoenzyme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
39
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(41 citation statements)
references
References 44 publications
2
39
0
Order By: Relevance
“…ROS molecules have been implicated in disrupting the activity of ACN by dismantling the Fe-S cluster (8). In addition, we have recently shown that both Al and Ga can promote oxidative stress in P. fluorescens (3,31). Thus, Al and Ga may produce an oxidative and Fe-starved environment, leading to a decrease in ACN activity.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…ROS molecules have been implicated in disrupting the activity of ACN by dismantling the Fe-S cluster (8). In addition, we have recently shown that both Al and Ga can promote oxidative stress in P. fluorescens (3,31). Thus, Al and Ga may produce an oxidative and Fe-starved environment, leading to a decrease in ACN activity.…”
Section: Discussionmentioning
confidence: 99%
“…Labile Fe can participate in the formation of ROS since this redox-active metal can donate and accept electrons. Previous work in our laboratory has shown that P. fluorescens cells exposed to either Al or Ga upregulate several antioxidant enzymes such as catalase and superoxide dismutase in order to cope with the pro-oxidant properties of these metals (3,31). In addition, enzymes involved in the production of NADPH display a generous increase in activity following exposure to either Al or Ga (17).…”
Section: Vol 74 2008mentioning
confidence: 92%
See 1 more Smart Citation
“…The ability of gallium to trigger an oxidative environment was revealed by other studies that demonstrated an overexpression of glucose-6-phosphate dehydrogenase and isocitrate dehydrogenase-NADPH, two NADPH producing enzymes. Also, catalase activity was shown to be diminished, Fe metabolism being severely braked by Ga toxicity [47]. A series of [Ga(LX) 2 ]ClO 4 compounds ((LX) -= deprotonated form of ligands containing pyridine and 4,6-substituted phenol moieties with X = methoxy, nitro, chloro, bromo, and iodo) displayed growth-inhibition activity on cisplatin-resistant human neuroblastoma cells [48,49].…”
Section: In Vitro Studiesmentioning
confidence: 99%
“…IncreasedproductionofH 2 O 2 was noticed due to Ga 3+ antibacterial action [51].However, Ga 3+ quenches the superoxide ion signal [51],anditisnotyetclearwhethertheROSsare the main reason or only a consequence of the Ga 3+ antibacterial action.…”
mentioning
confidence: 99%